The area of the surface of the silo that will be exposed to rain, wind, and sun is 450π square feet.
Explanation:Solution:
To find the area of the surface of the silo that will be exposed to rain, wind, and sun, we need to find the combined surface area of the hemisphere and the cylinder.
The radius of the circular base of the cylinder is half of its diameter, which is 10/2 = 5 feet.The height of the cylinder is 40 feet.The circumference of both the hemisphere and the cylinder is equal, so the circumference of the circular base of the cylinder is 2πr, where r is the radius of the base.The surface area of the hemisphere is equal to half of the surface area of a sphere with the same radius, which is 2πr²/2 = πr².The surface area of the circular base of the cylinder is πr².The surface area of the curved surface of the cylinder is the circumference of the base multiplied by the height of the cylinder, which is 2πr * 40.Now, let's calculate:
Surface area of the hemisphere = π(5)^2 = 25π square feetSurface area of the circular base of the cylinder = π(5)^2 = 25π square feetSurface area of the curved surface of the cylinder = 2π(5) * 40 = 400π square feetTo find the total surface area, we add up the surface areas of the hemisphere, the circular base, and the curved surface:
Total surface area = Surface area of hemisphere + Surface area of circular base + Surface area of curved surface = 25π + 25π + 400π = 450π square feet.
Therefore, the area of the surface of the silo that will be exposed to rain, wind, and sun is 450π square feet.
HELP ME PLEASE I DONT UNDERSTAND THIS PROBLEM!!!!! Worth 20PT
a ball is thrown with a slingshot at a velocity of 100 ft/sec at an angle 21 above the ground from a height of 5ft approximately how long does it take for the ball to hit the ground? acceleration due to gravity is 32 ft/s^2
Answer:
D) 2.37 seconds
Step-by-step explanation:
Took the test and got it wrong.
It takes 60 pounds of seed to completely plant a 10-acre field. How many acres can be planted per pound of seed
98 POINTS AND BRAINLIEST!!!!!!!!!!!
Hello!
I believe the answer is A) p(x) = 13x -20.
I hope it helps!
What is true about side AB and side AD?
Sharon wants to know the difference between the average amount she stacked and the average amount Diane stacked. Which operation would she use to find the difference?
For which angle is secant undefined?
30°
45°
180°
270°
Answer:
the answer is 180 degrees
Step-by-step explanation:
i used my head and my google maths
Algebra question ( Matrices and Determinants ) 20 points
Which expression is equivalent to x3 – 7x – 6?
How many times larger is 4 x 1016 than 5 x 108?
3(−4x) + 3(5) = 12
−12x + 15 = 12
−12x + 15 − 15 = 12 − 15
−12x = −3
x =
Answer: 1/4
don't forget to rate and thank plz.
katy buys ‘x’ cakes.
Gugu buys 3 times as many cakes as katy.
Deanna buys 2 more cakes than Katy.
Each cake costs 85p
The total of the cakes is £52.70
How many cakes did each girl buy?
Answer:
Katy bought 12 cakes
Gugu bought 36 cakes
Deanna bought 14 cakes
Step-by-step explanation:
Divide 2y2 + 8 by 2y + 4. Which expression represents the quotient and remainder?
Final answer:
To divide 2y² + 8 by 2y + 4, use long division to find the quotient and remainder.
Explanation:
To divide 2y² + 8 by 2y + 4, we can use long division. Here are the steps:
Divide the first term of the dividend by the first term of the divisor, which gives us y.
Multiply the entire divisor by y to get 2y² + 4y.
Subtract 2y² + 4y from the dividend 2y² + 8 to get 4.
Next, divide 4 by 2y + 4, which gives us 2.
Finally, we have a remainder of 0.
Therefore, the quotient is y + 2 and the remainder is 0.
what is the product? -9x(5-2x) 18x2 -45x -18x2-45x -18x-45 18-45x
Answer: A.
Step-by-step explanation:
The product of equation is 18x² - 45x.
What is linear equation?Each term in a linear equation has an exponent of 1, and when this algebraic equation is graphed, it always produces a straight line. It is called a "linear equation" for this reason.
Both linear equations with one variable and those with two variables exist.
Given equation -9x(5 - 2x)
product = -9x(5) - (-9x)(2x)
= -45x + 18x²
= 18x² - 45x
Hence the product is 18x² - 45x.
Learn more about linear equation;
https://brainly.com/question/29739212
#SPJ2
How to find the area of a triangle with a base of 32ft
Cindy and Giovanni plan to make spaghetti sauce. Cindy needs 4 3/4 pounds of tomatoes for her recipe. Giovanni needs 5 /34 pounds of tomatoes for his recipe. If they make both recipes, how many pounds of tomatoes do they need?
Answer:
[tex]10\frac{1}{2}\text{ pounds}[/tex]
Step-by-step explanation:
Given,
For a recipe,
Cindy needs tomatoes = [tex]4\frac{3}{4}[/tex] pounds,
While, Giovanni needs tomatoes = [tex]5\frac{3}{4}[/tex] pounds,
If they make both recipes,
Then, total tomatoes they need = [tex]4\frac{3}{4}+5\frac{3}{4}[/tex]
[tex]=\frac{19}{4}+\frac{23}{4}[/tex]
[tex]=\frac{42}{4}[/tex]
[tex]=10\frac{2}{4}[/tex]
[tex]=10\frac{1}{2}\text{ pounds}[/tex]
How can you prove a triangle is a right triangle? select one:a. use the distance formula to see if at least two sides are congruent.b. use the slope formula to see if any sides are perpendicular.c. use the distance formula to see if all three sides are congruent.d. use the slope formula to see if any sides are parallel?
please help me figure out this probability problem!!!
What is the 12th term of the sequence? 3, −9, 27, −81, 243, ...
531441
−531441
177147
−177147
Anna and Ryelin together have 895 songs downloaded. Ryelin has 177 more songs downloaded than Anna. How many songs do each of them have?
Solve the equation using square roots. 3x2 – 27 = 0
The value of X are x = 3 and x = -3. using square root.
What is square root?A square root can be regarded as a factor of a number in the sense that when that number is multiplied by itself, it gives the original number.
3x²– 27 = 0
⇒3x²= 27
⇒x²= 27/3
⇒x² = 9
⇒x = sqrt(9)
⇒ x =±3
Learn more about square roots here:-https://brainly.com/question/3617398
#SPJ2
solve the equation
3x-3= -18
The solution of the equation 3x-3= -18 is -5.
The algebraic expressions which are separated by an equal symbol in between them and with the same value is called is an equation
Example = 5x + 5 = 12
here, x is a variable and 5 and 12 are constants.
Given equation;
3x-3= -18
To find the value of x add 3 to both side, we get
3x = -18 +3
we get
3x = -15
divide both side by 3 we get
[tex]x = \dfrac{-15}{3}[/tex]
Convert in into the lowest form we get,
x = -5
The solution of the equation 3x-3= -18 is -5
Learn more about equations here :
https://brainly.com/question/29538993
#SPJ6
The volume of a right triangular prism is 72 cubic feet. The height of the prism is 9 feet. The triangular base is an isosceles right triangle.
Answer:
Step-by-step explanation:
What is the area of the triangular base? 8 square feet
What is the length of edge DF? 4 feet
Answer:
What is the area of the triangular base?
8 square feet
What is the length of edge DF?
4 feet
Step-by-step explanation:
just did the quiz on EDG
Seven of the 10 children at art camp make an average of 8 paintings. The remaining children make an average of 12 paintings. What is the average number of paintings made by children at the art camp? Enter your answer in the box.
Haley sings for $1,000 an hour. Her rate increases by 50% after midnight. If she sings one
night from 8:30 pm until 1:00 am, how much should she be paid?
a) $4500 b) $5000 c) $5500 d) $6000
A 3 inch wide border is wrapped around a rectangular prism. the length of the rectangular prism is 8 inches longer than its width. the surface area covered by the border is 383 square inches. what is the width of the rectangular prism? answer in units of inches.
The lateral area of a cone is 555 \pi cm^2 and the radius is 15.1 what is the slant height?
What value of c makes the trinomial below a perfect square x2 + 7x + c?
Rewrite as perfect squares
(x+3.5)²+ c-3.5²Answer:49/4
Step-by-step explanation:
Find the diameter of a circle whose equation is x2+(y−2)2=100x2+(y−2)2=100.
400
20
10
100
Help me please & thank ya
How do you complete the square of x^2-14x+33=0?
Final answer:
To complete the square for the equation x^2-14x+33=0, the constant 33 is moved to the other side, and the number needed to make the left side a perfect square trinomial, 49, is added to both sides, resulting in factoring and solving (x - 7)^2 = 16 to find x = 11 and x = 3.
Explanation:
To complete the square for the equation x^2-14x+33=0, you need to form a perfect square trinomial on the left side of the equation. First, you'll move the constant term to the right side:
x^2 - 14x = -33
Next, find the value that completes the square for the x-terms. This value is obtained by taking half of the coefficient of x (which is -14 in this case) and squaring it, giving us (-7)^2 = 49.
Add 49 to both sides of the equation:
x^2 - 14x + 49 = -33 + 49
x^2 - 14x + 49 = 16
Now, the left side of the equation is a perfect square trinomial, and can be factored into:
(x - 7)^2 = 16
To solve for x, take the square root of both sides:
x - 7 = [tex]\sqrt{16}[/tex]
x - 7 = +- 4
Finally, solve for x by adding 7 to both sides:
x = 7 +- 4
x = 11 or x = 3